Watchman - Rankin, Ian (London Orion Books, 2004)
Miles Flint is a spy whose last assignment led to the death of a foreign official in London, then to a short stint in jail. Convinced there is a mole in British intelligence, he sets out to find him--only to be waylaid by a routine mission to Belfast that may be his last.
Keywords: Northern Ireland--Belfast -- Moles (Spies)